InfoMinerva: interface do usuário para sistemas de software do domínio de patrimônio histórico - Moura, Milene Rosa de Almeida (Universidade Federal de São Carlos, 2018)
The patrimonial assets of the historic farms from São Paulo are rich sources of knowledge, impregnated with symbolic values, and represent the trajectory of the constituted power over time and the process of society. In order to facilitate the access to these assets, some public policy projects funded by FAPESP were developed: "Virtual Memory of São Carlos" (2004- 2008), "Cultural Patrimony of the State of São Paulo: Privileged Space for Research, Education and Tourism "(2008-2012) and" Criteria and methodologies for conducting an inventory of the rural cultural patrimony of São Paulo "(2012-2014). These projects resulted in two important products: the Information Description Standard, which allows the exhaustive cataloging of any type of property, and the Virtual Memory system, a web system composed of two subsystems, one for cataloging and one for access and navigation. The purpose of the present work is to create a prototype of a semi-functional interface for user, called InfoMinerva, to access data contained in the Virtual Memory web system, considering the premises of authors of the field of human-computer interaction. The target public considered to use the interface is composed of researchers and interested in patrimonial assets, not being prerequisite high level of knowledge in computer science. The study, initially exploratory, reviewed the literature on themes: historical patrimony, historical heritage in digital environments, human-computer interaction, quality and interaction criteria and principles, guidelines and heuristics aimed at the development of interfaces. By nature it is an applied research for proposing a solution for the availability of assets through the internet, relying on the prototyping technique. The first prototype, of low fidelity, was created on paper, which established the main elements of the interface, except colors, shapes, fonts, and the expected behavior at the time of interaction with the user. The evaluation of this stage took place in a formative way, through the guidelines of Nielsen and Tahir, making possible the correction of possible faults before the development of the interface in digital media. The second prototype, of high fidelity and semi-functional structure, was made using the Wix site creation platform, in which the elements designed in the first stage were applied, including colors, shapes and fonts. This step was evaluated through mixed questionnaires, adapted from the Questionnaire for user interaction satisfaction, and delivered to two groups of users: the first, made up of information professionals, information technology professionals and professionals in the area of historical heritage, and the second, of potential users. The analysis of the questionnaires, using statistical techniques (Likert scale, arithmetic mean, fashion, sample variance, standard deviation and Cronbach's alpha), showed that the general objective of the research was achieved, and the necessary interventions are mainly related to accessibility and responsive design.
InfoMinerva: user interface for historical heritage domain software systems
Keywords: Interação humano-computador; Prototipação; Patrimônio histórico; Ciência, tecnologia e sociedade; Human-computer interaction; Prototyping; Historical heritage; Science, technology and society; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS; OUTROS